The Relationship of Knowledge and Role of Nurse in Management with Hypertension Patients - Kurniati, Deni; Nugroho, Tri Adi; Wulandari, Rizki Yeni; Kurniawan, Moh Heri (An Idea Nursing Journal, 2024)
Hypertension is a disease that is increasing every year. Dieting for the risk of hypertension sufferers is still not implemented because many hypertension sufferers still have poor dietary behavior. This research aims to analyze the influence of education level and family support on diet in people at risk of hypertension using the self-care theory approach. The design of this research is Observational Analytical with a Cross Sectional approach. The sample taken using the Purposive Sampling technique with criteria for inclusion and exclusion at the Rajal Clinic was 80 respondents. This study collected data on education level and family support using a questionnaire sheet. The statistical test used is the multiple linear regression analysis test. The multiple linear regression analysis test results showed that family support had the most influence on diet in people at risk of hypertension, with a value of (0.001) with a coefficient of -.420. Based on this, family support can influence the diet of people at risk of hypertension, so there is a need for family support for people at risk of hypertension to reduce the risk of hypertension in people at risk of hypertension.